Turbulence Characteristic of Flow Near Laboratory Experiment Groin Fields - Wardhana, Pradipta Nandi (Department of Civil Engineering, Diponegoro University, 2018)
Groin is hydraulic structure utilized to protect riverbank from erosion. Groin will shift away flow. Area just downstream of groin structure will be occupied by low velocity flow hence there will be sediment deposition. Turbulence mechanism between primary flow region and groin field having important role in sediment exchange needs to be investigated. Instantaneous flow measurement was conducted in order to investigate turbulence relation between series groin under various groin spacing. Laboratory experiment employed turbulence flow having Reynolds number range between 31,935-32,500 and Froude number range between 0.051-0.053. A MicroADV 16-MHz was used to measure 3D instantaneous velocity. The experiment findings expressed that Reynolds stress involving vertical velocity and did not show any specific distributions except at the lowest measurement elevation, while Reynolds stress showed specific distributions. Turbulence value difference between groin field and primary flow region at upstream of the groin field was significant. As the area was getting downstream, area containing high turbulence was wider. This work indicated that bed shear stress value tended to grow at downstream area of groin field. High difference bed shear stress value between primary flow region and groin field seized second groin field and third groin field.